Key External Influences Affecting Consumers’ Decisions Regarding Food - Martinez-Ruiz, Maria Pilar; Gómez-Cantó, Carmen María (Frontiers in Psychology, 2016)
Among the numerous internal and external forces that compete for consumers’ attention in the context in which they buy their food, this paper will seek to provide a review of the most important external influences, such as the variables related to food itself. To this end, in addition to the food attributes traditionally identified in fields such as consumer behavior, it will give special consideration to the classification of food values. Although the influence of these variables on consumer decisions will depend on the individual, analyzing them will undoubtedly increase understanding of consumers’ decisions. Additionally, identifying and describing these variables will enable subsequent research on how they influence both consumer behavior and other key outcomes for producers, manufacturers, and retailers in the food industry, such as satisfaction, trust, and loyalty.